3-Ls: A MODEL FOR TEACHING YOUNG LEARNERS - Chuzaimah Dahlan Diem (TEFLIN, 2011)
The fact that EFL literacy in Indonesia is still low led me to conduct this study to cultivate reading habits and increase literacy skills of young learners. Using the 3-Lsâlibraries, literature, and literacyâas an instructional model, the study involved five methods: Informational Text Structures; Online Resources; Partnership with Librarians; Big6; and Literature Circles. The sample consisted of 200 fifth graders divided equally into five groups, each of which was also divided into experimental and control groups. Each of tThe experimental groups was taught for three months using one method. All the students in both groups were given English tests and a questionnaire before and after the experiment. The results showed that the experimental groups outperformed the control groups with a significant mean difference of 21.73 on literacy skills and 10.15 on reading habits. Using regression analysis, it was also found that 3-Ls as a whole had given a significant contribution to both studentsâ reading habits (R2 0,793) and literacy skills (R 0,943) with the highest percentage contributed by every method was reading skill. However, in spite of demonstrating significant effects on studentsâ literacy, these methods still did not bring the studentsâ literacy to an acceptable level. A factor that might contribute to the low achievement of their English literacy was that the 3-Ls model requires optimal facilities.